Analysing the Resilience of Fortified Settlements from the Perspective of Community Capital: The Case of Pujing Community in the Ancient Acropolis, Yongning, Quanzhou - Shao-Chuan Zhu; Rung-Jiun Chou (Land)
In recent years, religious activities have been employed to promote community industrial transformation and territorial revitalisation in fortified settlements along the southeast coast of China. This paper adopted a qualitative approach to study the community of Pujing, an ancient acropolis in Quanzhou, with the aim of analysing how community capital constructed through faith promotes community resilience. The findings of the study are as follows: (1) Pujing is a community system and organisation built upon religious beliefs; (2) the community utilises religious beliefs to construct a community network platform to promote community capital building and industrial transformation; and (3) religious activities are an integral part of daily life in the community, serving as a form of community capital. This paper argues that the Pujing community promotes community capital building by enhancing community cohesion and participation through religious activities. Ultimately, this fosters the ‘spiralling-up’ of community resilience.